Use of Regional Languages in Indonesian Language Learning at Kampar Regency Elementary Schools - Muhammad Amin (IJLHE: International Journal of Language, Humanities, and Education, 2024)
This research aims to analyze the use of regional languages ​​in student communication in Indonesian language learning at Kampar Regency Elementary Schools. The research method used is field research with a qualitative research method approach and descriptive data analysis. Data collection was carried out by interviews, observation, and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions/verification. The results of the research are that the use of regional languages ​​in Indonesian language learning in Kampar Regency elementary schools has great potential to improve students' language understanding and skills. The integration of regional languages ​​helps explain complex concepts and enriches the learning process. However, it is important to balance the use of regional languages ​​and Indonesian so that both are supported. With the support of teacher training, development of teaching materials, and community involvement, the use of regional languages ​​can be an effective strategy for improving the quality of education in Kampar Regency.